Practice importance of the results of population studies on the single umbilical artery - Yu.V. Trusov; V.A. Kramarskiy; N.I. Faizullina (РМЖ. Мать и дитя, 2020)
Yu.V. Trusov, V.A. Kramarskiy, N.I. Faizullina Irkutsk State Medical Academy of Professional Education — Branch of the Russian Medical Academy of Continuous Professional Education, Irkutsk, Russian Federation This paper discusses the clinical importance of the isolated single umbilical artery (iSUA). It was demonstrated that iSUA is an independent risk factor for perinatal death. The authors report that iSUA results in higher risk of the manual removal of the placenta, atonic post-partum hemorrhage, and postpartum uterus curettage. iSUA is closely associated with esophageal and anorectal atresia or stenosis and trisomy 13 and trisomy 18. Isolated iSUA (i.e., in the lack of fetal malformations) is associated with the Battledore placenta. It is also emphasized that iSUA fetus should be monitored using an ensemble of diagnostic techniques (ultrasound, Doppler, cardiotocography) for the early recognition of placental hypoperfusion, intrauterine growth restriction, and fetal acidosis. The authors postulate that a worsening of the cerebroplacental ratio or placental perfusion indices as well as abnormal cardiotocography are the indications to C-section in iSUA. In spontaneous delivery, the continuous electronic monitoring of fetal heart beat is recommended for the prompt diagnosis of its impairment, the prevention of maternal hemorrhages, and the detection of fetal abnormalities postnatally. The management of iSUA risk factors includes smoking cessation, the control of diabetes and hypertension. Keywords: single umbilical artery, malperfusion, placenta, middle cerebral artery, perinatal mortality, trisomy. For citation: Trusov Yu.V., Kramarskiy V.A., Faizullina N.I. Practice importance of the results of population studies on the single umbilical artery. Russian Journal of Woman and Child Health. 2020;3(4):242–247. DOI: 10.32364/2618-8430-2020-3-4-242-247.